The effect of temperature and water on the mechanical properties of wool fibres investigated with different experimental methods - Aksakal, Baki; Alekberov, Vilayet (KOREAN FIBER SOC, 2009)
The tensile and durability properties of single wool fibres were investigated with tensile testing method and lever equipment giving the results examined by Zhurkov's kinetic equation under the effects of temperatures and water. Moreover, Differential Scanning Calorimetry (DSC) method was applied to determine denaturation and degradation peaks and corresponding enthalpies of wool fibre. It was shown that with increasing temperature, tensile properties and durability of the wool fibres decreased considerably. A great decrease on tensile properties was seen at temperatures higher than similar to 200 A degrees C after which a denaturation doublet of alpha-keratin and a wide thermal degradation peak were observed in DSC diagrams. Moreover, the wet fibres obtained lower tensile characteristics except breaking extension which increased by 9 % and 20 % for the fibres kept in water for one h and one month, respectively. However, the breaking extension of the fibre tested in water increased greatly by 73 % which indicates the important role of water molecules on the intermolecular interactions during stretching. The weakening effect of water molecules on the structure was also shown by DSC result of wet wool fibres at which the thermal degradation enthalpy of alpha-keratin and other histological components decreased by 22 %. The changes of the tensile and durability characteristics of wool fibres were compared and discussed in detail based on Zhurkov's equation and intermolecular interactions.
Keywords: Wool fibre; Tensile property; Lifetime; Stress-strain curve; Microfibril; KERATIN FIBERS; RELATIVE HUMIDITY; THERMAL-ANALYSIS; PROTEIN FIBERS; HUMAN HAIR; TRANSFORMATION; COMPOSITES; CELLULOSE; YARNS; MODEL; Materials Science; Polymer Science